MODEL EVALUASI KINERJA DARI USAHA KECIL : SUATU PENDEKATAN PERENCANAAN STRATEGIS DI KOTAMADYA MALANG - Indah Mustikowati, Rita; Nu Graha, Andi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2010)
This research is aim to investigate the influence between strategic planning that used by a small firms through internal and eksternal environment analysis process. The subject of the research conducted to small firms owner which located in Malang. Total sample that used to this studi is 125 respondent, determined by using purpossive sampling. Primary data were collected and analyzed by using SEM technics analysis. This tools used to know the relationship and the influence which conducted by construct variables to the independent variables. The research found that strategic planning has a influence to the strategic which determine by the small firms owner. This study found that strategic planning which consist of internal and external factors having a positive relationship with evaluation and control, but both of them don’t have an influence significanly. Internal environment has a positive relationship and significanly influence to the evaluation and control. The other side, external environment has a negative relationship and significnly don’t have an influence with evaluation and control. The other founded from this study is strategic planning which consist of internal and external environment has a positive relationship and significanly not influence with a small firms strategy. From this study know that internal and external environment has a positive relationship with small firms strategy. Internal environment not significant influnce to the small firms strategy, but eksternal environment have it. Finnaly, this study also show that small firms strategy has an influence to the evaluation and controlling.